Deadly Pandemia: Monkeypox Disease, a Case Study - Peace Abiodun Olajide; Oluwakemi Semiloore Omowumi; Darasimi Deborah Okunlola; Babatunde Oluwafemi Adetuyi (African Journal of Advanced Pure and Applied Sciences, 2022)
Short Communication paper